Weak Social Networks in Late Life Predict Incident Alzheimer's Disease: The Kuakini Honolulu-Asia Aging Study. Issue 4 (8th October 2022) - Kallianpur, Kalpana J; Masaki, Kamal H; Chen, Randi; Willcox, Bradley J; Allsopp, Richard C; Davy, Philip; Dodge, Hiroko H
Abstract: Background: We assessed 10-year longitudinal associations between late-life social networks and incidence of all-cause dementia (ACD), Alzheimer's disease (AD), and vascular dementia (VaD) in Japanese-American men. Methods: We prospectively analyzed, from baseline (1991–1993) through 1999–2000, 2636 initially nondemented Kuakini Honolulu-Asia Aging Study participants who remained dementia-free during the first 3 years of follow-up. Global cognition was evaluated by the Cognitive Abilities Screening Instrument (CASI); depressive symptoms by the 11-item Center for Epidemiologic Studies Depression (CES-D) Scale; and social networks by the Lubben Social Network Scale (LSNS). Median split of LSNS scores defined weak/strong social network groups. A panel of neurologists and geriatricians diagnosed and classified dementia; AD and VaD diagnoses comprised cases in which AD or VaD, respectively, were considered the primary cause of dementia. Results: Median (range) baseline age was 77 (71–93) years. Participants with weak (LSNS score ≤29) versus strong (>29) social networks had higher age-adjusted incidence (in person-years) of ACD (12.6 vs. 8.7; p = .014) and AD (6.7 vs. 4.0; p = .007) but not VaD (2.4 vs. 1.4; p = .15). Kaplan–Meier curves showed a lower likelihood of survival free of ACD (log-rank p < .0001) and AD ( p = .0006) for men with weak networks. In Cox proportional hazards models adjusting for age, education, APOE ɛ4, prevalent stroke, depressive symptoms, and CASI score (all at baseline), weak networks predicted increased incidence of ACD (hazard ratio [HR] = 1.52, p = .009) and AD (HR = 1.67, p = .014) but not VaD ( p > .2). Conclusion: Weak social networks may heighten the risk of dementia and AD, underscoring the need to promote social connectedness in older adults.